The Social Comparison Scale: Testing the Validity, Reliability, and Applicability of the Iowa-Netherlands Comparison Orientation Measure (INCOM) on the German Population - Simone Schneider; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Social comparisons are an essential source of information about the self. Research in social psychology has shown individual variation in the tendency toward comparison with other people's opinions and abilities, raising the question of whether social comparisons are driven by psychological dispositions. To test the empirical validity of this proposition, Gibbons and Buunk (1999) created an instrument that measures the tendency to engage in social comparison and captures central aspects of the self, the other, and the psychological interaction between the two. The Iowa-Netherlands Comparison Orientation Measure (INCOM) comprises 11 core items that have been tested in the United States and the Netherlands. To date, however, no attempt has been made to implement this instrument in a large-scale survey of the German population. To fill this gap, the core items of the INCOM scale were integrated into the 2010 SOEP (Socio-Economic Panel Study) pretest. This paper analyzes the validity of the INCOM scale and discusses potentials for shortening the instrument for continued use in large-scale population surveys. Exploratory and confirmatory factor analysis as well as scale validation tests (invariance tests combined with external validation techniques) produce acceptable results and confirm the measurement instrument as valid and effective. With regard to shortening the questionnaire, a six-item scale is recommended, which shows excellent model fit and proves to be a reliable and efficient indicator to grasp individual dispositions towards social comparison.
Keywords: D31; D63; Z13; 330; Social comparisons; relative evaluations; reference groups; validity tests; SOEP; Sozialpsychologie; Interpersoneller Nutzenvergleich; Panel; Soziale Beziehungen; Deutschland